2020
DOI: 10.14202/vetworld.2020.764-767
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Salmonella Typhimurium from village chickens based on invA and spvC genes

Abstract: Aim: This study aimed to identify Salmonella enterica serovars by polymerase chain reaction (PCR) based on virulence genes invasion A (inv A) and Salmonella plasmid virulence C (spvC). Materials and Methods: DNA extraction of eight bacteria isolates was done using the PowerSoil® DNA Isolation Kit. The amplification of invA and spvC genes was done using conventional PCR. The positive PCR products were purified using the GeneJET Purification Kit and then sequenced using ABI 3730 XL automated genetic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
0
1
2
Order By: Relevance
“…Using conventional PCR approach, 9 out of 36 of microbiologically Salmonella positive isolates were detected invA-positive in free range chicken which is in agreement with the results of previous studies suggested that PCR amplification of invA gene made a reliable rapid diagnosis of salmonella spp. in the samples compared with samples as evaluated by the traditional cultural and biochemical methods (El-Sharkawy et al, 2017;Siala et al, 2017) in pig, ruminant and chicken (Scholz et al, 2001;Al-Iedani et al, 2015;Akinola et al, 2019;Mkangara et al, 2020). In the present study, the overall rate of Salmonella isolates in the free-range chicken was significantly lower than that of the commercial raised chicken (Harvey et al, 2011;Jajere et al, 2019).…”
Section: Discussioncontrasting
confidence: 54%
“…Using conventional PCR approach, 9 out of 36 of microbiologically Salmonella positive isolates were detected invA-positive in free range chicken which is in agreement with the results of previous studies suggested that PCR amplification of invA gene made a reliable rapid diagnosis of salmonella spp. in the samples compared with samples as evaluated by the traditional cultural and biochemical methods (El-Sharkawy et al, 2017;Siala et al, 2017) in pig, ruminant and chicken (Scholz et al, 2001;Al-Iedani et al, 2015;Akinola et al, 2019;Mkangara et al, 2020). In the present study, the overall rate of Salmonella isolates in the free-range chicken was significantly lower than that of the commercial raised chicken (Harvey et al, 2011;Jajere et al, 2019).…”
Section: Discussioncontrasting
confidence: 54%
“…BLASTn merupakan fitur pada BLAST yang dapat membandingkan suatu query sequence yang diinginkan dengan database sekuen nukleotida yang ada pada database NCBI (Hennebry et al, 2012). Penelitian yang mengaplikasikan fungsi ini antara lain dilakukan oleh Mkangara et al (2020) menggunakan BLASTn untuk mengidentifikasi informasi serovar pada isolat ayam kampung, hasil BLAST menunjukkan isolat merupakan Salmonella enterica serovar Typhimurium strain 14028 dan Salmonella enterica subspecies enterica serovar Typhimurium strain 14028. Bano et al (Hung & Weng, 2016).…”
Section: Hasil Dan Pembahasanunclassified
“…Gen target yang banyak digunakan pada penelitian deteksi dan identifikasi adalah gen invasif InvA (Melati, Nurjanah, & Rahayu, 2022). Penggunaan gen ini sebagai target potensial adalah karena gen ini ditemukan spesifik pada strain Salmonella (Mkangara, Mbega, & Chacha, 2020). Selain menggunakan gen invA Penggunaan gen target lain dilakukan Nurjanah et al (2018) dengan menggunakan gen STM dan plasmid virulen Prot6E spesifik untuk Salmonella Typhimurium dan Salmonella Enteritidis dan tidak mendeteksi serovar lain (Muhsinin, Sulastri, & Supriadi, 2019).…”
Section: Hasil Dan Pembahasanunclassified